The Implementation of Constructivism Theory to Develop Religious Character on Students with Special Needs - Beni Azwar (STAI Hubbulwathan Duri, 2023)
This study aims to determine the application of humanist theory in the development of religious character in inclusive schools. The research method used is grounded theory design which aims to emphasize conceptual thinking and theory formation from the application of constructivism theory in developing religious character in inclusive schools. This is because; (1) the limitations of children with disabilities in developing their potential, (2) constructivism theory gives students freedom in constructing ideas related to religious character, and (3) the obstacles of children with disabilities in constructing ideas, ideas and knowledge. The results of the research on students' knowledge construction process in inclusive schools are very varied. Children with cognitive disabilities and autism have difficulty constructing knowledge, but it is more a process of repeated habituation. For children with disabilities, there is no problem in constructing knowledge but difficulty in implementing it in the form of behavior. Visually impaired children need other people as sensory aids and have no problems in behavioural practice, while speech and hearing impaired children have difficulty adjusting to normal learning patterns, because they cannot hear and speak and need teachers who can sign language. So cognitive and mental limitations hinder the process of constructing knowledge of religious character, for the implementation of character values is carried out by habituation of patterned behaviour by strengthening the process.